1996
DOI: 10.1007/s002640050041
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular manifestations of congenital insensitivity to pain with anhydrosis

Abstract: We report the case history of a boy who suffered from congenital insensitivity to pain with anhydrosis. We discuss the orthopaedic disorders occurring in 21 cases reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…However, in our study, joint dislocations and infections had no apparent relationship with age. Previous studies have not documented the age of onset of bone disorders in CIPA and similar conditions [14,15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in our study, joint dislocations and infections had no apparent relationship with age. Previous studies have not documented the age of onset of bone disorders in CIPA and similar conditions [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…Although skeletal-system complications are more common in the lower limbs, almost all bones and joints may be affected. Szöke et al [14] reported that 58 % of patients with CIPA had osteoarticular disorders of the feet and ankles, 53 % of the knees, and 26 % of the hips. Bar-On et al [15] reported that in 31 fractures in patients with congenital insensitivity to pain, 28 occurred in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, the first step in the diagnosis of CIPA syndrome is consideration of the clinical presentation based on the combination of three basic signs: insensitivity to pain, anhidrosis, and mental retardation [ 3 , 4 ]. Other possible signs may be associated: impaired temperature sensation [ 5 ], facial alterations [ 6 ], mandibular osteolysis [ 7 ], dental caries [ 6 ], and premature tooth loss [ 6 ]; repetitive soft tissue and osseous infections of hematogenous origin [ 33 ], mainly caused by S. aureus [ 25 ]; self-mutilating behavior [ 7 ]; occasional microcephaly [ 5 , 24 ]; urine and fecal incontinence [ 11 ]; growth disturbances; and heterotopic ossification [ 7 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal complications are frequent in HSAN-IV and -V, and include repeated fractures and joint dislocations, arthritis and osteomyelitis, avascular necrosis, and Charcot arthropathy, mainly in the lower extremities. [16][17][18][19] A review of Japanese patients with HSAN-IV showed that fractures are frequent between 1 and 7 years of age, whereas other complications have no apparent age relationship. 20 Fractures and dislocations develop in HSAN-IV and -V, even without any apparent trauma or following minor trauma, such as short falls (Fig.…”
Section: Musculoskeletal Complicationsmentioning
confidence: 99%